SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN PINJAMAN PADA BSI CABANG SIGLI MENGGUNAKAN METODE COMPLEX PROPORTIONAL ACCESSMENT (COPRAS) BERBASIS WEB - Rahmatullah; Husaini; Zulfa Razi (Sagita Academia Journal, 2023)
Loans are the provision of services by one party to another where the service is returned within a certain period along with money as a form of remuneration. Funding requirements can be obtained from own capital or loan capital, in this study Designing an application that can perform eligibility for BSI customers in making loans Implementing the web-based complex proportional Accessment (COPRAS) method with the hope of being able to provide detailed information for eligibility of customers in granting loans by bank BSI sigli branch. based on the assessment of the criteria namely administration, Loan History, Business Feasibility and Loan Length, the conclusion in this study is that the decision support system for eligibility for granting loans to the Sigli BSI branch using the web-based Complex Proportional Accessment (COPRAS) method can assist in determining eligibility customers lending, so that lending is precise and accurate